Case Study of the Uber Failure in China: A Technoethical Analysis - Zhen, Yu (Université d'Ottawa | University of Ottawa, 2018)
Technology and digitalization today have greatly accelerated the process of globalization and introduced new business approaches and concepts. Drawing on the notion of a sharing economy, the ride sharing economy introduced by Uber has created social controversy and debate. When Uber expanded to the market in China from 2013 to 2017 with the venture ending in failure, it marked the first time to introduce the concept of a ‘sharing economy’ to China. The ride sharing economy brought by Uber created economic, political, cultural, and social upheaval within society. Guided by the technoethical approach, a case study on the failure of Uber in China was conducted using a systematic literature review of essential research articles and news coverage from 2013 to 2017. Case study findings uncover the following main themes connected to Uber’s localization in China: safety, privacy, morals and ethics, environments, regulation and legislation, urban plan, labor identity, and labor fairness. The technoethical analysis reveals a gap between technology and ethical awareness, a need to pay more attention to ethical consequences, and a need for government laws and regulations to keep pace with new e-business technologies. This case study contributes new insight into Uber in China and the ride sharing economy from an ethical perspective.